Injuries according to the percentage of adult height in an elite soccer academy - Monasterio, X.; Gil, S. M.; Bidaurrazaga-Letona, I.; Lekue, J. A.; Santisteban, J.; Diaz-Beitia, G.; Martin-Garetxana, I.; Bikandi, E.; Larruskain, J. (Journal of Science and Medicine in Sport, 2021)
Objectives: This study aimed to ascertain if there is a defined pattern of injury related to the percentage of attained adult height and classify injuries according to maturity status bands. Design: Prospective cohort study. Methods: From 1998-2019, 63 elite male soccer players of at least the U12 category from a Spanish LaLiga club`s academy were followed until reaching their final height. Medical staff recorded injuries following the FIFA consensus and measured height 2-3 times per season. The percentage of adult height at which each injury occurred was calculated using the player`s closest height to the injury and his final adult height. Injuries were classified in maturity bands, pre-peak-height-velocity (PHV) <88%, circa-PHV 88%-96%, and post-PHV >96%. Results: There were 509 injuries among the 63 players. Growth-related injuries occurred at a median (IQR) of 91.2% (86.7%-95.2%) of adult height, predominating in pre-PHV and PHV bands. Muscle injuries predominantly occurred at post-PHV, with 77.78% of those conditions occurring within that time frame and at 98.7% (96%-99.5%) of adult height. Likewise, knee and ankle joint/ligament injuries predominated at post-PHV (87% and 65% of total cases, respectively) occurring at 99.0% (97.9%-99.9%) and 98.4% (89.2%-99.4%) of adult height, respectively. Conclusions: Injuries follow a specific pattern according to the percentage of adult height.